Pharyngeal bulb prosthesis and speech outcome in patients with cleft palate - Pegoraro-Krook,Maria Inês (2022)
Abstract Introduction: Individuals with cleft palate can present with velopharyngeal dysfunction after primary palatoplasty and require a secondary treatment due to insufficiency. In these cases, the pharyngeal bulb prosthesis can be used temporarily while awaiting secondary surgery. Objective: This study aimed to investigate the outcome of treatment of hypernasality with pharyngeal bulb prosthesis in patients with history of cleft palate presenting with velopharyngeal insufficiency after primary palatal surgery. We hypothesized that the use of the pharyngeal bulb prosthesis is an effective approach to eliminate hypernasality related to velopharyngeal insufficiency in patients with cleft palate. Methods: Thirty speakers of Brazilian Portuguese (15 males and 15 females) with operated cleft palate, ages ranging from 6 to 14 years (mean: 9 years; SD = 1.87 years), participated in the study. All patients were fitted with a pharyngeal bulb prosthesis to manage velopharyngeal insufficiency while they were awaiting corrective surgery to be scheduled. Auditory-perceptual analysis of speech recorded in the conditions with and without pharyngeal bulb prosthesis were obtained from three listeners who rated the presence or absence of hypernasality for this study. Results: Seventy percent of the patients eliminated hypernasality while employing the pharyngeal bulb prosthesis, while 30% still presented with hypernasality. The comparison was statistically significant (p < 0.001). Conclusion: The use of the pharyngeal bulb prosthesis is an effective approach to eliminate hypernasality related to velopharyngeal insufficiency.